Dance Movement Therapy for Clients With a Personality Disorder: A Systematic Review and Thematic Synthesis - Kleinlooh, S. T.; Samaritter, R. A.; van Rijn, R. M.; Kuipers, G.; Stubbe, J. H (Frontiers in Psychology, 2021)
People with a personality disorder (PD) suffer from enduring inflexible patterns in cognitions and emotions leading to significant subjective distress, affecting both self- and interpersonal functioning. In clinical practice, Dance Movement Therapy (DMT) is provided to clients with a PD and although research continuously confirms the value of DMT for many populations, to date there is no overview of DMT literature for clients with PD. Therefore, we conducted a systematic literature review and a thematic synthesis to offer an overview of existing studies concerning the effects of DMT for clients with a PD and detailed information on DMT interventions for this client population. A systematic search was conducted across the following databases; EMBASE, MEDLINE, PubMed, WEB OF SCIENCE, PsycINFO/OVID and SCOPUS following the PRISMA guidelines. The Critical Appraisal Skills Program for qualitative studies was used to rank the quality of the articles. The standards of the Oxford Centre for Evidence-based Medicine were applied to determine the level in the hierarchy of best evidence. Quantitative content analysis was used to identify components of the intervention: intended therapeutic goals, therapeutic actions leading to these goals and suggested therapeutic effects following from these actions. In a final step, a thematic synthesis approach was applied to formulate and analyse overarching themes. Among 421 extracted articles, four expert opinions met the inclusion criteria. Six overarching themes were found for DMT interventions for PD: self-regulation; interpersonal relationships; the integration of self; processing experiences; cognition, and expression and symbolization in movement/dance. Only within the themes self-regulation, interpersonal relationships and cognition could all intervention components be identified. Findings suggest that dance movement therapists working with clients with a PD focus in their interventions on body-related experiences, non-verbal interpersonal relationships and, to a lesser extent, cognitive functioning. No systematic description of DMT approaches for PD was found. Future studies are needed to support the development of intervention strategies, with a focus on the components of the aforementioned themes including dance-informed interventions. Although this study offers detailed information, further research is necessary to explore which mechanisms are active in DMT to create a positive change in clients with a PD.